Sosialisai Tentang Pentingnya Vitamin C Untuk Kesehatan Tubuh Dan Donor Darah Di Kecamatan Medan Helvetia, Kota Medan - Monica Suryani; Manahan Situmorang; Natanael Priltius (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
The important role of ascorbic acid or Vitamin C in the body is for metabolic processes and tissue repair. Antioxidants from Vitamin C can help protect cells from free radicals. Vitamin C can protect skin and produce collagen. Collagen is a natural protein in the body that forms the structure of the skin, whose production can decrease due to free radicals and aging. Vitamin C can maintain collagen production so that skin looks healthy and firm. Therefore, Vitamin C can work to maintain beauty and health. The highest daily dose of vitamin C is 1,000 milligrams/day. In this service activity, two activities were carried out separately, namely socialization about the importance of Vitamin C for body health and blood donation in Medan Helvetia District, Medan City to provide information to residents of Medan Helvetia District regarding the importance of Vitamin C for body health. Blood donation is also carried out to have many impacts both on the health of the donor and the recipient. This activity was also carried out to increase awareness regarding the health benefits of consuming Vitamin C.